STATISTIK PENDIDIKAN SEBAGAI INSTRUMEN EVALUASI DAN PENGAMBILAN KEPUTUSAN DALAM PEMBELAJARAN - Lamretta, Nanda Akti; Simbolon, Ici Sry Ulina; Dalimunthe, Riska Romayani; Calista, Venecia (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
Educational statistics is an important tool in data-driven decision-making in education. However, many teachers and researchers experience misconceptions related to statistics, which can lead to errors in data collection, analysis and interpretation of results. This study aims to identify common errors that occur in educational statistics, including misconceptions often experienced by teachers, and provide solutions to overcome these problems. Using a literature study approach, we analyzed various sources to provide insights into these errors and how to avoid them. It is hoped that the results of this study can improve the quality of educational research and make a more significant contribution to educational policy development. Misconceptions in education statistics not only impact research results, but can also influence decisions taken by stakeholders in education. Therefore, it is important to recognize and address these errors so that the data analysis conducted can be more valid and reliable. The study also provides recommendations for improving the understanding of statistical techniques used in educational research. With the right steps, it is expected that the quality of educational research can be improved and make a greater contribution to the development of data-based educational policies.